Hegemonia Neoliberal Lulista - Luz, Luiz Fernando Ribeiro Da (2015)
This dissertation analyzes the specifics of the Brazilian neo-liberal development model during the Lula era. That period provided an expansion of Brazilian capitalism, whose main character is the expansion of neoliberal social relations, achieved through microeconomic measures that which fall within the social life through a set of policies that made possible an improvement in living conditions of the impoverished populations. This kind of politics surpass, at least for a time, the transformations of macroeconomic policies that marked the predecessor period. In order that this development model had some successful concatenation in the domestic space, it was necessary to develop into the political and ideological superstructure an agreed set of interests between different social forces, but especially among the different factions of the ruling class. We call this development model of "concerted regulation", whose ultimate purpose is to maintain and to develop the level of neoliberal reproduction, strengthening the conservative forces and deepening the social inequality. The period in which the Partido dos Trabalhadores keeps ahead of the Federal Government was marked for a special hegemonic configuration, which be called here "Lula's neoliberal hegemony": a kind of golden age of bourgeois hegemony in Brazil. The Lula's neoliberal hegemony is defined by the entry of the "lulo-petismo" into the dominant political group. Lulo-petismo means a set of social forces of popular origin and left political traditions that has undergone a profound transformismo adding to the "concerted regulation" a passive and active consensus of the masses, while strengthened political and economic forces of the Brazilian bourgeoisie, without changing the external vulnerability of the economy.